Understandings, readiness and challenges of post-endemic COVID-19 e-learning implementation among university students / Hazwani Abdul Wahab and Siti Nur Izyandiyana Ab. Hadi - Abdul Wahab, Hazwani; Ab. Hadi, Siti Nur Izyandiyana (Faculty of Communication & Media Studies, 2024)
The advent of e-learning or online learning has emerged as an alternative educational tool in reaction to the global outbreak of the Covid-19 pandemic in 2020, which hindered traditional face-to-face learning for students and educators. Diverse digital apps are developed to enhance the e-learning process for those studying in a university or a school. The utilization of e-learning is progressively gaining traction across diverse global industries. Students across various academic levels, from elementary to advanced, have begun utilising e-learning tools. Nevertheless, the extent of understanding, readiness, and challenges faced by these students during e-learning remains uncertain. Hence, the researcher aims to determine the students' understanding level regarding their e-learning experience at the university. The researcher also aims to examine the level of readiness and identify the challenges that university students face in the e-learning process. The study was conducted on a total of 305 students from Universiti Sultan Azlan Shah (USAS) in Kuala Kangsar, Perak, as well as students from Universiti Teknologi Mara (UiTM) Alor Gajah Campus in Lendu, Melaka. The results of the survey show that the participants are strongly committed to learning and have a positive understanding of e-learning. However, there are some challenges related to access to technology and insufficient support at home. While there is an overall positive outlook for the future of e-learning, there are concerns about disinterest and engagement issues. Future research should focus on strategies for addressing technological disparities, enhancing support systems, and understanding factors that influence sustained engagement in e-learning. Additionally, exploring the impact of specific interventions on overcoming the challenges identified in this study could provide valuable insights for improving the effectiveness and inclusivity of e-learning experiences.